Environmental pollution and protection - Garg, M. R.; Bansal, V. K. (Vijay Kumar), 1943-; Tiwana, N. S. (New Delhi : Deep & Deep Publications, 1995)
Contributed research papers.
Includes bibliographical references and index.
Keywords: Environmental policy; Environmental policy -- India; Pollution -- Environmental aspects; Environmental law -- India